1995
DOI: 10.1200/jco.1995.13.5.1062
|View full text |Cite|
|
Sign up to set email alerts
|

Perceptions of cancer patients and their physicians involved in phase I trials.

Abstract: Cancer patients who participate in phase I trials are strongly motivated by the hope of therapeutic benefit. Altruistic feelings appear to have a limited and inconsequential role in motivating patients to participate in these trials. Cancer patients who participate in phase I trials appear to have an adequate self-perceived knowledge of the risks of investigational agents. However, only a minority of patients appear to have an adequate understanding of the purpose of phase I trials as dose-escalation/dose-dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
361
4
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 459 publications
(392 citation statements)
references
References 27 publications
25
361
4
2
Order By: Relevance
“…For example, PSC 833 is targeted to the patients who are potentially resistant to vinca alkaloids or anthracyclines with multidrug resistance (MDR) overexpression. The result of our study, in which about half of patients did not appear to understand the purpose of phase I trials completely, seems similar to the result reported by Daugherty et al (1995) who asked both open-ended and closed questions (Daugherty et al, 1995). While it is absolutely essential that patients understand the purpose as well as the details of the method and possible risks and benefits of the clinical trials, patients who have incurable cancer may not be receptive to information on the theoretical basis of clinical trials and they are focused more on how these will affect them, not the scientific methodology.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…For example, PSC 833 is targeted to the patients who are potentially resistant to vinca alkaloids or anthracyclines with multidrug resistance (MDR) overexpression. The result of our study, in which about half of patients did not appear to understand the purpose of phase I trials completely, seems similar to the result reported by Daugherty et al (1995) who asked both open-ended and closed questions (Daugherty et al, 1995). While it is absolutely essential that patients understand the purpose as well as the details of the method and possible risks and benefits of the clinical trials, patients who have incurable cancer may not be receptive to information on the theoretical basis of clinical trials and they are focused more on how these will affect them, not the scientific methodology.…”
Section: Discussionsupporting
confidence: 88%
“…The possibility of treatment-related risks and side-effects are well recognized after informed consent is given even by patients in phase II1III studies (Penman et al, 1984). It should be emphasized that these results are in accord with those found in a study in the United States (Daugherty et al, 1995). Almost all patients in our institution seemed to have understood the voluntary nature of participation in phase I trials.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…15 However the majority of patients are (appropriately) concerned primarily with finding the best possible treatment for their disease. 15,39,40 In the absence of other barriers, a patient who believes that the best possible treatment option is to be found in a clinical trial is more likely to participate in that clinical trial. 33 …”
Section: Understanding Barriers To Clinical Trial Participationmentioning
confidence: 99%